Berberine increases adipose triglyceride lipase in 3T3-L1 adipocytes through the AMPK pathway. Issue 1 (December 2016) - Jiang, Dongqing; Wang, Dianhui; Zhuang, Xianghua; Wang, Zhanqing; Ni, Yihong; Chen, Shihong; Sun, Fudun
Abstract Background Obesity is closely related to the metabolism of triacylglycerol (TG) in adipocytes. Adipose triglyceride lipase (ATGL) and hormone-sensitive lipase (HSL) are rate-limiting enzymes that control the hydrolysis of TG. Effects on ATGL and HSL to increase lipolysis may counteract obesity. Berberine (BBR) is a compound derived from the Chinese medicine plant Coptis chinensis. In the present study we show the effects of BBR on ATGL and HSL and explore the potential underlying mechanisms of these effects. Methods The TG content in cells was measured using a colorimetric assay. The expressions of HSL, ATGL and GPAT3 were evaluated by Western-blotting. The expression of ATGL was also evaluated by real-time PCR and radioimmunoassay. Compound C, an inhibitor of AMP-activated protein kinase (AMPK), was used to explore the possible pathway that involved in the effect of BBR on ATGL. Results TG content of differentiated 3T3-L1 cells was significantly decreased by more than 10% after treated with BBR. In differentiated 3T3-L1 adipocytes, BBR increased the expression of p-HSL and ATGL, and these effects were time-depended (p <0.01 ). The effect of BBR on ATGL expression could be abolished by Compound C which suggested that AMPK pathway was involved in the effects of BBR on p-HSL and ATGL. Conclusions BBR could increase the expression of ATGL and therefore stimulate basal lipolysis in mature adipocytes through the associated mechanisms related to the AMPK pathway.